Solution structure of allergenic 2 S albumins. (November 2002) - Pantoja-Uceda, D.; Bruix, M.; Santoro, J.; Rico, M.; Monsalve, R.; Villalba, M.
Abstract : The NMR solution structures at different levels of refinement of three different 2 S albumin seed proteins, the recombinant pronapin precursor from Brassica napus, the recombinant RicC3 from Ricinus communis and the methionine-rich protein from sunflower ( Helianthus annuus ), are described. The resulting common structure consists of a bundle of five α-helices, folded in a right-handed superhelix. The structure is very similar to that of other plant proteins: the hydrophobic protein from soybean, non-specific lipid transfer proteins and amylase/trypsin inhibitors. Analogies and differences in the structures of these families, as well as their possible relationship to allergenicity, are discussed.